TCR γ4δ1-Engineered αβT Cells Exhibit Effective Antitumor Activity - Kangxia He; Hongqin You; Yuxia Li; Lianxian Cui; Jianmin Zhang; Wei He (BMC, 2016)
Abstract T cell engineering with T cell receptors (TCRs) specific for tumors plays an important role in adoptive T cell transfer (ATC) therapy for cancer. Here, we present a novel strategy to redirect peripheral blood-derived αβT cells against tumors via TCRγ4δ1 gene transduction. The broad-spectrum antitumor activity of TCRδ1 cells in innate immunity is dependent on CDR3δ1. TCRγ4δ1-engineered αβT cells were prepared by lentiviral transduction and characterized by analyzing in vitro and in vivo cytotoxicity to tumors, ability of proliferation and cytokine production, and potential role in autoimmunity. Results show that TCRγ4δ1 genes were transduced to approximately 36% of polyclonal αβT cells. TCRγ4δ1-engineered αβT cells exhibited effective in vitro TCRγδ-dependent cytotoxicity against various tumor cells via the perforin-granzyme pathway. They also showed a strong proliferative capacity and robust cytokine production. TCRγ4δ1-engineered αβT cells neither expressed mixed TCR dimers nor bound/killed normal cells in vitro. More important, adoptive transfer of TCRγ4δ1-engineered αβT cells into nude mice bearing a human HepG2 cell line significantly suppressed tumor growth. Our results demonstrate a novel role for TCRγ4δ1 in gene therapy and ATC for cancer.